LITERATURE STUDY ON THE CONTRIBUTION OF SOCIAL ECONOMIC LAW TO SOCIAL JUSTICE - Loso Judijanto (Adisam Publisher, 2025)
This literature study explores the contribution of social economy law to the implementation of social justice in the context of economic regulation and policy. Through the analysis of various literature sources, it is found that social economic law serves as an important framework that seeks to encourage the fair redistribution of resources and ensure protection for vulnerable groups. Policies such as minimum wage setting, social security, and corporate social responsibility are analysed as important instruments in creating a more economically just society. The study also underlines the importance of social economy law in strengthening social inclusion and economic stability geared towards sustainability and equity. However, it was also found that to achieve optimal effectiveness, policy adjustments that are responsive to changing social and economic dynamics are required. The findings confirm that the success of social economy law in achieving social justice depends on comprehensive, inclusive and adaptive policy implementation.